Hepatoprotective effect of the methanol extract of Luffa cylindrica fruit on carbon-tetrachloride induced chronic liver injury - Oyeyemi, Ifeoluwa T.; Akanni, Oluwabukola O.; Adaramoye, Oluwatosin A.; Bakare, Adekunle A. (Acta Biologica Szegediensis, 2023)
Luffa cylindrica (Linn) commonly called sponge gourds has both medicinal and nutritional properties. It is used traditionally for the management of liver diseases. Herein, we investigated the hepatoprotective effect of the crude methanol extract of L. cylindrica fruit in rats chronically exposed to carbon tetrachloride (CCl4). Male rats were exposed to CCl4 twice a week for six weeks and the extract was administered five times a week for six weeks. Markers of liver toxicity, antioxidant enzymes and liver peroxidation were evaluated and histological analysis of the liver was carried out. Significant reduction in serum markers (ALT, AST and ALP), increase in antioxidant enzyme and reduction in lipid peroxidation compared to CCl4 were observed in rats exposed to both CCl4 and the extract. CCl4-induced liver lesions were ameliorated by the extract. These show the protective effect of the methanol extract of L. cylindrica on CCl4-induced chronic liver injury in rats.